Stuck in the Ways of the South: How Meritocracy, Bureaucracy, and a One-Size-Fits-All Approach to Child Welfare fails Nunavut’s Children - Johnston, Patricia (First Peoples Child & Family Review, 2011)
Based on qualitative research that explored the experiences of social workers in Nunavut’s child welfare system, this paper examines the current approach to child welfare in light of a critical report issued by Canada’s Auditor General in March 2011. Through a discussion of meritocracy, this study highlights the problematic approach to child welfare used by the Government of Nunavut, particularly in their reliance on Qallunaat or nonInuit social workers. The territory’s current child welfare system, modeled on child welfare systems operating throughout southern Canada, does little to change the status quo and instead serves to maintain the colonial power structure in place for the last 50 years. This study determined that a unique and culturally relevant approach to child welfare is needed in Nunavut and Inuit traditional knowledge is essential is the move towards this important goal2.